2005
DOI: 10.1007/s00737-005-0104-x
|View full text |Cite
|
Sign up to set email alerts
|

Group interpersonal psychotherapy for postnatal depression: a pilot study

Abstract: We conducted a pilot study to assess the potential effectiveness of group interpersonal psychotherapy (IPT-G) as a treatment for postnatal depression (PND). The study was also established to test a treatment manual for IPT-G, assess the acceptability of this format for participants and test a recruitment strategy for a randomised controlled trial. 18 mothers diagnosed with PND participated in 2 individual session and 8 sessions of group IPT. A two-hour psychoeducational session was also held for the partners o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…71 Additionally, 2 small open studies of group IPT demonstrated significant reduction of depression in women with PPD. 72,73 …”
Section: Treatment Of Ppdmentioning
confidence: 99%
“…71 Additionally, 2 small open studies of group IPT demonstrated significant reduction of depression in women with PPD. 72,73 …”
Section: Treatment Of Ppdmentioning
confidence: 99%
“…However, there was a high attrition rate (6 out of 17), and the study was also limited by small sample size, lack of a control group, and lack of an independent rater. Similarly, Reay et al treated, in an open pilot trial, 18 women diagnosed with postpartum depression with 8 group IPT sessions, as well as two individual and one partner session 104. Depressive symptoms decreased significantly, and these gains were maintained at three months.…”
Section: Discusssionmentioning
confidence: 99%
“…The high attendance rates of 70%, the increase in the number of participants following the recommendation of the program by the initial participants to other Iraqi women are indicators of the global acceptability of the treatment amongst this cultural group. In comparison, attrition rates of 63, 17, and 55% were found in other group interventions for PND (Brugha et al, 2000; Milgrom et al, 2005; Reay et al, 2005). The current results support Foster and Mash (1999) dimensions of treatment acceptability, in which low dropout rates, high rates of attendance and the ease of dissemination of the intervention can be used as consumer ratings of global treatment acceptability.…”
Section: Discussionmentioning
confidence: 85%